Delivering a female with missing cervix: a case report - Kumar, Mahendra; Pawar, Preeti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Authors received a case in our casualty, 26 years old, G2P1L1, with full term pregnancy, spontaneous conception, previous normal vaginal delivery, with labour pain. On evaluation, she was having uterine contraction, fetal heart rate normal, vitally stable, with no cervix on per speculum and per vaginal examination, with solid globular mass per rectum. She was shifted to emergency operation theatre with provisional diagnosis of uterine rupture or rectal perforation or pelvic mass. After delivering a live baby, uterus was intact, but there was an impacted mass in pouch of Douglas, it was a twisted ovarian mass, sent for histopathology examination. Post-operative period was uneventful, and patient was discharged with healthy baby with corrected pelvic anatomy.